The Role of Knowledge and Attitude in Improving Disaster Preparedness Among Health Workers: a Study in Donggala Regency - A. Ferina Herbourina Bonita; Ummu Khaerat Rahmawan; Roswati, Roswati; Yusniar Anggraeny; A. Suci Setiani Annisa; Rifdah Wardani (Jurnal EduHealth, 2025)
Natural disasters such as the earthquake in Central Sulawesi, particularly in Donggala Regency, have a significant impact on public health, making the preparedness of healthcare workers crucial. This study combines the results of three studies conducted at Punggava Tompe, Kanamaseha Batusuya, and Kami Seivi Lembasada Community Health Centers to identify factors associated with disaster preparedness among healthcare workers. All three studies used a quantitative design with a cross-sectional approach and involved total sampling, with 72, 57, and 70 respondents, respectively. Data analysis was performed using univariate and bivariate methods using the Chi-square test. The synthesis results showed differences in findings across locations. Two studies (Tompe and Batusuya) indicated that knowledge was not significantly related to preparedness (p>0.05), while attitude was significantly related (p<0.05). In contrast, the study in Lembasada found that both knowledge (p=0.004) and attitude (p=0.000) were significantly related to preparedness. Overall, a consistent attitude plays a crucial role in improving disaster preparedness, while knowledge yields varying results depending on the context and conditions of the community health center. It is recommended that community health centers strengthen training, outreach, and disaster simulation programs, as well as increase the knowledge and positive attitudes of health workers to address disaster threats in earthquake-prone areas.